The Role of Teachers in the Digital Era Navigating the Transformation of Quality Education Towards the 2030 SDGs - Evanirosa (Seumike : Society Progress Journal, 2025)
The role of teachers in the digital era has become increasingly vital in navigating the transformation of quality education towards achieving the 2030 Sustainable Development Goals (SDGs). This article explores the paradigm shift in education driven by technological advancements and how teachers adapt to remain relevant as agents of change. By integrating technology into teaching methods, teachers can create inclusive, interactive, and 21st-century-relevant learning environments. This study also highlights challenges faced by teachers, such as the digital divide, the need for technological training, and curriculum adaptation. Using a qualitative analysis approach, the article concludes that teachers' roles extend beyond educators to include facilitators, innovators, and moral guides. With appropriate policy support, digital-based educational transformation is expected to accelerate the achievement of SDG targets, particularly in providing quality education for all.